Tracing Digital Fragmentation at the User Level: Gen Y & Gen Z from a European Perspective - Lichy, Jessica; Racat, Margot (Management international / International Management / Gestiòn Internacional)

(untitled) (HEC Montréal, 2021)
This study compares the usage of Social Networking Sites (SNS) in two non-Anglophone settings. A longitudinal mixed-method approach was designed to gather data face-to-face with Gen Y and Gen Z participants in Lyon (France) and St Petersburg (Russia) between 2011 and 2018, by means of survey, forum and focus groups. The initial differences observed in user behaviour were no  longer apparent by 2018. Noticeably similar user behaviour reflected converging SNS consumption. From the findings, we identify socio-technical changes that influence SNS usage, in order to produce a typology of user behaviours for identifying user segments.